Recognition of Japanese culture in Javanese culture unggah-ungguh through school library brochures - Hascaryo Pramudibyanto (Vocational College of Diponegoro University, 2023)
Family is the most important place, which introduces and applies values and culture. The socialization process in the family is done early and always evaluated if something goes wrong, in order to form a social order, speech acts, and good behavior. Values or rules in Javanese society are known as unggah-ungguh in terms of behavior, appreciation and respect for others, with regard to degree or age. The form is unwritten and involves more aspects of taste and appropriateness. School-age teenagers in the category of adolescents and experiencing cultural shifts, not all of them are able to carry out Javanese cultural manners, which in Japanese culture there are cultural values that can be emulated. Javanese cultural manners are not specifically taught in schools, so there is a need for media that specifically provides information about this. Brochures on Javanese cultural manners and Japanese politeness culture can be obtained in the form of cultural recognition brochures. The cultural values that can be recognized include not monopolizing the conversation, introducing oneself, greeting directly, bowing, thanking and apologizing, collective culture when eating together, pouring drinks for others, and avoiding pointing or staring at others. The respondents of this study agreed to develop a media brochure on Javanese and Japanese cultural recognition. By developing a media brochure on the recognition of Japanese culture into Javanese culture, school students can understand the value of the culture and implement it into their daily lives. The development of this culture sheet product is cheap, with media specifications tailored to the financial capabilities of the institution.